Sportwissenschaft - Weissenfels A; Teschler M; von Stengel S; Kohl M; Kemmler W (Deutsche Zeitschrift für Sportmedizin)
Background: Low back pain (LBP) has a high priority in our predominately sedentary society. The aim of this meta-analysis of present data was to evaluate the effect of whole-body electromyostimulation (WB-EMS) on LBP in sedentary older people with relevant pain.Methods: The present analysis based on four recently-conducted randomized controlled WB-EMS trials (RCT). All of the trials included participants 60 years+ and used WB-EMS-protocols with comparable stimulation parameters (1.5 sessions/week, 16-25min/session, bipolar, 85Hz, 350s, 4-6s impulse/4sec impulse-break) applied for 14-52 weeks. All the studies defined strength as a primary or secondary study-endpoint. We included only subjects with relevant LBP frequency in the present analysis (5 on a 0-7 scale). Ofthe 36 men (n=11) and women (n=25) sampled, 17 were participants ina WB-EMS-group and 19 subjects were in the corresponding control group (CG). Results: At baseline, no group differences with respect to LBP intensity and frequency were observed. Pain intensity improved significantly in the WB-EMS (p<.001) and did not change (p=.834) in the CG. Group differences for pain intensity were significant (p=.012). LBP frequency,however,improved significantly in the WB-EMS (p<.001) and the CG (p=.042). Differences between WBEMS and CG were borderline non-significant (p=.050).Conclusion: WB-EMS appears to be an effective training tool for reducing LBP. Nonetheless, effectiveness, feasibility and sustainability of this training technology should be addressed more intensivelyby further, more dedicated RCTs.KEY WORDS: Chronic Nonspecific Low Back Pain, WB-Electromyostimulation, Pain Intensity and Frequency, Resistance Exercise